Extending Hirshfeld‐I to bulk and periodic materials 1. Issue 5 (24th August 2012) - Vanpoucke, Danny E. P.; Bultinck, Patrick; Van Driessche, Isabel
Abstract In this work, a method is described to extend the iterative Hirshfeld‐I method, generally used for molecules, to periodic systems. The implementation makes use of precalculated pseudopotential‐based electron density distributions, and it is shown that high‐quality results are obtained for both molecules and solids, such as ceria, diamond, and graphite. The use of grids containing (precalculated) electron densities makes the implementation independent of the solid state or quantum chemical code used for studying the system. The extension described here allows for easy calculation of atomic charges and charge transfer in periodic and bulk systems. The conceptual issue of obtaining reference densities for anions is discussed, and the delocalization problem for anionic reference densities originating from the use of a plane wave basis set is identified and handled. © 2012 Wiley Periodicals, Inc.